Prognostic Value of Third Cervical Vertebra Skeletal Muscle Index in Oral Cavity Cancer: A Retrospective Study. (12th January 2021) - Chang, Sheng‐Wei; Hsu, Cheng‐Ming; Tsai, Yuan‐Hsiung; Chang, Geng‐He; Tsai, Ming‐Shao; Huang, Ethan I.; Tsai, Yao‐Te
Abstract : Objectives/Hypothesis: To assess the prognostic utility of third cervical vertebra skeletal muscle index (C3 SMI) measured from preoperative head and neck computed tomography (CT) in patients with oral cavity squamous cell carcinoma (OSCC). Study Design: Retrospective study. Methods: We retrospectively reviewed the medical records of 125 patients who underwent primary curative surgery for OSCC between 2009 and 2017. Their preoperative C3 SMI was calculated by adjusting the C3 cross‐sectional area delineated on head and neck CT by body height squared. A Cox proportional hazard model was employed to identify prognostic factors, and a novel nomogram based on C3 SMI was built for individualized survival prediction. Results: In Kaplan–Meier analysis, high C3 SMI was significantly associated with higher 5‐year disease‐free survival (DFS) and overall survival (OS) than low C3 SMI. In multivariate analysis, low C3 SMI was an independent risk factor for poor DFS and OS (hazard ratio [HR]: 2.197; 95% confidence interval [CI], 1.170–4.512, P = .032 and HR: 2.143; 95% CI, 1.232–3.728, P = .007, respectively). The concordance‐index (C‐index) of the nomogram based on C3 SMI was 0.814 for OS, higher than that of the nomogram based on tumor–node–metastasis staging alone (C‐index = 0.731). Conclusions: C3 SMI might serve as a novel prognosticator in OSCC patients undergoing curative surgery, and the nomogram based on C3 SMI might provide good prognostic discrimination ability for individualized survival prediction. Level of Evidence: IV Laryngoscope, 131:E2257–E2265, 2021